HUBUNGAN FAKTOR DEMOGRAFI, PERIODE DAN LAMA KERJA DOKTER TERHADAP KETERLAMBATAN PENGISIAN RESUME MEDIS PASIEN BPJS DI RUANG RAWAT INAP RSAU DR. ESNAWAN ANTARIKSA - Nuraini, Nia; K, Gatot Soeryo; Yusmaini, Hany (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2016)
More than 50% of the medical resume at airforce hospital (RSAU) were not returned in due time which caused claim verifcation delayed by social security administrator (BPJS). The purpose of the study was to find out the relation of physician’s demography factors, work periode and duration in terms of the delays in completing medical resume. Cross sectional design was implemented and secondary data was obtained from medical records. Logistic regression analysis showed thedominant factors of the delays in completing medical resume amongstage, sex, work period and work load was sex.